Persian emotion elicitation film set and signal database. (February 2022) - Shalchizadeh, Fatemeh; Shamekhi, Sina; Naghdi Sadeh, Reza; Darvish, Abbas
Abstract: Emotions are associated to human central and peripheral nervous system activity and visual stimulus has the potential to invoke emotions. In the field of emotion analysis and recognition, films are widely used due to their similarity to real-life situations and various film sets have been collected in different languages. In this work, we present the PEEFS (Persian Emotion Elicitation Film Set) collection. According to the authors' knowledge, Persian Emotion Elicitation Film Set (PEEFS) is the first emotion elicitation Persian film set that has been collected and validated by an 88-person population using an online server-based website created in this work. We have watched 84 most-watched Iranian films to trim emotional segments, and the final set consists of 21 film clips, duration from 20 to 100 s, with discrete labeling based on six basic emotions and ratings in two dimensions of arousal and valence. These 21 film clips have the highest intensity at each target emotion. In addition, emotion scores of the film clips are also included. This database can be used to stimulate emotions and to design automatic emotion recognition systems at different levels. In this work, a signal database has been provided by recording 2 channels of forehead EEG (Fp1 and Fp2) and 8 peripheral signals that include ECG lead II, GSR, trapezius and zygomatic EMG (tEMG and zEMG), vertical EOG (vEOG), finger pulse, Respiratory signal and skin temperature, using the PEEFS film set and selected film clips from the previous English and French databases.